FEATURES OF ESTABLISHING COOPERATION BETWEEN PARTICIPANTS OF THE EDUCATIONAL PROCESS OF THE PRESCHOOL EDUCATION INSTITUTION - Lutsenko, Victoria (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article is devoted to the problem of establishing cooperation between participants in the educational process of a preschool education institution. Based on the analysis of philosophical, psychological and pedagogical literature, the state of problems is revealed. The purpose of the article is to study the peculiarities of establishing cooperation between the participants of the educational process in the preschool education institution as a condition for ensuring its quality. The purpose of the article determined the following tasks: 1) to carry out an analysis of the problem in the pedagogical theory and practice of preschool education institutions; 2) to investigate the state of establishment of cooperation between the participants of the educational process of the preschool education institution as a means of ensuring the quality of preschool education.To achieve the goal and solve the set tasks, the following research methods were used: analysis of philosophical, psychological-pedagogical and methodical literature on the research problem; methods of pedagogical diagnostics (teacher questionnaires).The article substantiates the pedagogy of partnership as a factor in the formation of effective interaction of participants in the educational process of a preschool education institution and a means of ensuring its quality. The essence of the concept of “partnership pedagogy” is revealed, the principles and criteria on which partnership pedagogy is based are indicated.The present requires the teacher to work for the future, to be ahead of his time, which involves improving professional skills, constant analysis of pedagogical activity and making corrections in accordance with social demands throughout the entire professional activity. All this actualizes the search for effective ways of professional development of educators, is considered as one of the means of developing the competence of pedagogical partnership to ensure the quality of preschool education. Ensuring the equality of all participants in the educational process, partnership pedagogy is a direction of pedagogical thinking and practical activity aimed at democratization and humanization of the pedagogical process of a preschool education institution. The implementation of the principles of partnership pedagogy creates the basis for ensuring the quality of preschool education.The conducted research mainly confirms the opinions of scientists that partnership pedagogy is an important factor in the effective interaction of participants in the educational process of a preschool education institution.The practical significance of the article is that its materials can be used in the organization of the educational process of preschool education institutions for monitoring the internal quality system.